Peningkatan Kemampuan Motorik Halus Anak Usia Dini melalui Penggunaan Media Loose Part - Wulansari, Resi; Nur, Lutfi; Yamin, Alfian Azhar (AS-SABIQUN, 2025)
The low level of fine motor skills in early childhood has become a concern in early childhood education, particularly due to the limited use of varied, meaningful, and developmentally appropriate learning media. This study aims to determine the effect of using loose part media on the development of fine motor skills in young children. A quantitative method with a pre-experimental one-group pretest-posttest design was employed, involving 10 Group B students at RA Assalam, selected through purposive sampling. The research instrument consisted of monitoring documents based on indicators of fine motor development in early childhood, aligned with developmental achievement standards. The results showed an increase in the average score from 27.40 before the intervention to 42.50 after the intervention. The Wilcoxon test yielded a significance value of 0.005 (p < 0.05), indicating a significant difference between pretest and posttest results. Thus, the use of loose part media proved effective in enhancing the fine motor skills of early childhood learners. These findings highlight the importance of implementing flexible, exploratory, and child-friendly media to create enjoyable learning experiences and support children’s holistic development.